Efektivitas Ekstrak Tumbuhan Rawa sebagai Biopestisida Plutella xylostella dalam Skala Laboratorium - Asikin, Syaiful; Alwi, Muhammad; Khairullah, Izhar; Abdillah, Muhammad Helmy (Jurnal Teknologi Agro-Industri, 2022)
Cabbage caterpillars can attack all stages of plant growth in the vegetative and generative phases. In the concept of integrated pest control, the use of chemical insecticides is the last alternative, so an environmentally friendly control technology is needed. Swampland has the potential of plants that can be extracted as active ingredients for pest control. The results of the literature study showed that there were several types of potential wetland plants that contained the active ingredient of hydrocarbon derivative compounds which were effective in controlling Plutella, but of the 13 types of plants, a study was conducted on their effectiveness in controlling Pluttela xylostella larvae is very necessary. The purpose of this study was to determine the effectiveness of various types of wetland plants as effective botanical insecticides in controlling Pluttela xylostella on a laboratory scale. The results showed that there were 13 types of swamp plants that could be effective botanical insecticides in controlling Pluttela xylostella. The mortality of Pluttela xylostella larvae at 48 hours of observation was high in the treatment of plant extracts of Piper sarmentosum, Tithonia diversifolia, and Ziziphus spina-christi with a percentage of 68%. Therefore, it is necessary to conserve these wild plants so that these plants do not become extinct.